Primerjava parametrov svetlobnih razmer na raziskovalnih ploskvah - Čater, Matjaž (Gozdarski vestnik, 2011)
Using the analysis of hemispherical photos we defined radiation parameters on ten research plots in adult and homogenous stands. We compared summer and winter parameter values of stand openness (%) and leaf area index (LAI) in the years 2009 and 2010 and compared them with ocular estimations of leaf area defoliation on the same locations. The values of the differences between the summer and winter values matched best with the ocular defoliation data, separately for plots with coniferous and deciduous trees. Radiation measurements are more objective than ocular estimations and can represent a starting point for stand condition comparison. Their advantage is a fast measurement and evaluation in a relatively short period which enables provability, comparison of larger stand parts or selected objects.
Keywords: gozdovi; svetlobno sevanje; listna površina